PERLINDUNGAN HUKUM KONSUMEN ATAS KETERLAMBATAN PENGIRIMAN BARANG OLEH PERUSAHAAN EKSPEDISI - Sibarani, Jenny L.; Hulman Panjaitan; Daniel Suhardiman (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
This normative juridical study, based on the Convention on the Rights of the Child (Presidential Decree No. 36/1990), examines legal protection of children by parents under Indonesian law and the use of restorative justice in parental child abuse cases. It finds that violence against children is a crime under Article 80 of the UUPA, with parental status increasing penalties. While restorative justice aims for restoration, it is deemed inapplicable to violent parental child abuse, as parents should prioritize the child’s best interests. The study recommends legal officials optimally apply Law No. 23/2002 on Child Protection to effectively implement its legal threats.